Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1093/ije/dyp261
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic change and the increased prevalence of autism

Abstract: Changes in practices for diagnosing autism have had a substantial effect on autism caseloads, accounting for one-quarter of the observed increase in prevalence in California between 1992 and 2005.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
221
0
12

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 380 publications
(247 citation statements)
references
References 17 publications
6
221
0
12
Order By: Relevance
“…As mentioned earlier, our results support the idea that DSM-IV-TR criteria may broaden the identification of ASD among lowerfunctioning individuals and suggest that individuals with high functioning autism were not identified in clinical settings or brought to clinical attention for autism-related concerns during the 1980s. Work is under way to estimate the potential contributions of diagnostic substitution, changes in diagnostic criteria, and other factors to determine the extent to which each of these contributes to the increase in prevalence (King and Bearman 2009;Liu et al 2010). …”
Section: Discussionmentioning
confidence: 99%
“…As mentioned earlier, our results support the idea that DSM-IV-TR criteria may broaden the identification of ASD among lowerfunctioning individuals and suggest that individuals with high functioning autism were not identified in clinical settings or brought to clinical attention for autism-related concerns during the 1980s. Work is under way to estimate the potential contributions of diagnostic substitution, changes in diagnostic criteria, and other factors to determine the extent to which each of these contributes to the increase in prevalence (King and Bearman 2009;Liu et al 2010). …”
Section: Discussionmentioning
confidence: 99%
“…Around 25% of the rise in autism over the past two decades can be attributed to what he calls "diagnostic accretion". He could see from the medical records that some children who would have been diagnosed as mentally retarded a decade ago are now given a diagnosis of both mental retardation and autism 11 . Another 15% can be accounted for by the growing awareness of autism -more parents and paediatricians know about it 12 .…”
Section: Filling the Gapmentioning
confidence: 99%
“…21 The study showed total PedsQL and cognitive functioning was better in children whose parents had history of consanguineous marriage. This might be due to the fact that the consanguineous family usually possessed better family functioning than their non consanguineous counterpart that might influence the child's life quality.…”
Section: Discussionmentioning
confidence: 91%